(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
The research has been conducted on clay-loam soil. The soil has been exposed to three levels of pressure (P0, P1, P2) that equals (0, 187.5, 307,4 ) Kpa respectively, the treatments O0 have loosened, the treatment O1, O2 have fertilized with two levels during the loosening, as well as the control treatment O0. The study showed a significant increase in bulk density by increasing the pressure and the highest value in the treatment was P2O00= 1.46 g/cm3.. On the other hand the production of soybean seeds was significantly decreased by average 301 Kg/h at the pressure P1 compared with uncompressed treatment, and by average 577 Kg/h at the pressure P2. The loosening leads to a significant increase by average 467 Kg/h at P0, 844 Kg/h at P1 and 301 Kg/h at P2 compared with uncompressed treatment. As well as the loosening and fertilizing at the levels O1 and O2 leads to a significant increase in the productivity at the treatment P0 compared with uncompressed-unfertilized treatment by average 954 kg/h, 1424 kg/h respectively, also an increase at the treatment P1 465 kg/h, 1147 kg/h respectively and an increase at the treatment P2 670kg/h, 904 kg/h respectively. The percentage of oil was significantly decreased by average 1.69 % at P1 and 2.91% at P2 compared with P0 . The treatments which have exposed only to mechanical loosening showed a significant increase in the percentage of oil by average 3.99 % at P0 and 1.22 % at P2, while the increasing at P1 was not significant by average 0.24%. The loosening and fertilizing at the levels O1 and O2 leads a significant increasing at P0 by rate 5% and 5.26% respectively, also leads to a significant increasing at P1 by rate 3.23% and 4.26% respectively and a significant increase at P2 by rate 3.07% and 4.14% respectively. The results of protein analysis showed a significant decrease in its percentage by rate 4.49% at P1, 8.29% at P2. The fertilizing during the loosening at both levels O1 and O2 leads to a significant increase at P0 treatments by rate 4.9% and 9.87% respectively, also a significant increase at P1 treatments by rate 5.23% and 11.07% respectively and a significant increase at P2 treatments by rate 7.47% and 9.1% respectively أجريت الدراسة على تربة طينية لومية، حيث تم ضغط التربة بثلاث مستويات(P0، P1 ، P2) وتساوي (0، 187,5 ، Kpa (307.4 على الترتيب، ثم تم إجراء معاملات تفكيك ميكانيكي O0 وأيضاً معاملات تسميد بمستويين أثناء التفكيك O1و O2 إضافة للشاهد O00. وبينت الدراسة ارتفاع الكثافة الظاهرية معنوياً مع زيادة الضغط المطبق وبلغت أعلى قيمة لها في المعاملة P2O00 =1.46غ/سم3. وبالنسبة للإنتاج انخفضت غلة بذار فول الصويا معنوياً بمعدل 301 كغ/ه وذلك عند الضغط P1 مقارنة بالمعاملة غير المضغوطة P0، وبمعدل 577 كغ/ه عند P2، وأدى التفكيك لزيادة معنوية بلغت 467 كغ/ه عند P0و841 كغ/ه عند P1و301 كغ/ه عندP2 مقارنة بالمعاملة غير المفككة. كذلك ادى التفكيك والتسميد معاً بالمستويين O1و O2 إلى زيادة معنوية في الانتاجية مقارنة بالمعاملة غير المفككة وغير المسمدة وذلك بمعدل954 و 1424كغ/ه على الترتيب وذلك عند المعاملة P0، وزيادة قدرها 465و 1147كغ/ه أيضاً على الترتيب عند P1 ، وزيادة قدرها 670و 904كغ/ه أيضاً على الترتيب عندP2 ، كذلك انخفضت نسبة الزيت معنوياً بمقدار 1.69% في معاملات P1 و بمقدار 2.91% في معاملات P2 مقارنة بالمعاملة P0، وتظهر المعاملات التي تم تفكيكها ميكانيكياً فقط زيادة معنوية في نسبة الزيت بمقدار3.99 %في المعاملة P0 وبمقدار 1.22 % في المعاملة P2 في حين كانت الزيادة غير معنوية في المعاملة P1 وبلغت 0.24% فقط، وأدى التفكيك والتسميد معاً بالمستويين O1 و O2 لزيادة معنوية بمقدار 5% و5.26%على الترتيب وذلك في المعاملات P0، كذلك أدى لزيادة معنوية بمقدار3.23 % و 4.26% على الترتيب في المعاملة P1 وزيادة معنوية بمقدار3.07 % و 4.14% على الترتيب في المعاملة P2. وبالنسبة لتحليل البروتين فتبين انخفاض نسبته معنوياً وبمقدار 4.49% عند الضغط P1وبمقدار %8.29 في معاملات الضغطP2 ، كذلك أدى التسميد أثناء التفكيك معاً بالمستويين O1 و O2 لزيادة معنوية بمقدار 4.9% و 9.87% على الترتيب وذلك في المعاملات P0، و زيادة معنوية بمقدار5.23 % و 11.07% على الترتيب وذلك في المعاملة P1، وزيادة معنوية بمقدار7.47 % و 9.1% على الترتيب في المعاملة P2.